2018
DOI: 10.1016/j.artd.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Primary lower limb joint replacement and tranexamic acid: an observational cohort study

Abstract: BackgroundThis work aimed to evaluate the efficacy and safety of routine tranexamic acid (TXA) use in elective orthopaedic lower limb joint replacement surgery.MethodsThis retrospective cohort study included all primary hip or knee replacement procedures by a single surgeon over a 6-year period. TXA was introduced during the study period as part of an enhanced recovery after surgery strategy.ResultsOf the 673 procedures, 446 cases (66.3%) received TXA. The median length of stay was 5 days (2-69) and 6 days (3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Paradoxically, in their analysis 90 days after hip and knee arthroplasty, Jørgensen et al found that fall-related hospital readmissions were due to physical activity and extrinsic factors other than surgery because of patient success and intent to return to a normal level of activity [ 24 ]. As emerged from all of the studies examined in this review, in turn, all of these interventions reduce the LOS as patients could be discharged sooner without increasing the risk of complications (References [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxically, in their analysis 90 days after hip and knee arthroplasty, Jørgensen et al found that fall-related hospital readmissions were due to physical activity and extrinsic factors other than surgery because of patient success and intent to return to a normal level of activity [ 24 ]. As emerged from all of the studies examined in this review, in turn, all of these interventions reduce the LOS as patients could be discharged sooner without increasing the risk of complications (References [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Resultsmentioning
confidence: 99%
“…Designation of positive, neutral and negative outcome for each examined study. (References [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ...…”
mentioning
confidence: 99%